PENGARUH NaCl DAN AMELIORAN ORGANIK Azolla pinnata TERHADAP N-TOTAL, pH TANAH, SERTA BOBOT KERING TANAMAN PADI (Oryza sativa L.) PADA INCEPTISOLS JATINANGOR - Khoiriyyah, Luluatul; Setiawati, Mieke Rochimi; Suriadikusumah, Abraham (Jurnal Agroekoteknologi, 2017)
The high content of NaCl in soil may lead to nutrient imbalance and inhibit the Nitrogen uptake by plants. Azolla pinnata can be used as an organic ameliorant to help plant roots in absorbing nutrients and enhancing the number of available N for plants. The aim of this research was to ascertain whether Azolla pinnata as organic ameliorant gave the significant difference on the enhancement of N content of soil, pH of soil, and dry weight of rice plant on various salinity level of soil and also to find out if Azolla pinnata could suppress salinity stress at certain salinity. The experiment was conducted at the Greenhouse of Faculty of Agriculture Universitas Padjadjaran, Jatinangor and also at the Laboratory of Soil Fertility and Plant Nutrion, Departement of Soil Science and Land Resources on November 2016 until March 2017. The experimental design used was Randomized Completely Block Design with 8 treatments and 4 replications. The treatment was consisted of without the organic ameliorant Azolla pinnata, and with the application of Azolla pinnata on salinity level 0, 2, 4, 6 mmhos cm-1. The results showed that the application of NaCl and Azolla pinnata gave the significant difference on soil pH, and dry weight of plant. The application of Azolla pinnata is not able yet to suppress the rice symptom of salinity stress at 2, 4, and 6 mmhos cm-1 on the enhancement of dry weight of plant. The application of Azolla at salinity 6 mmhos cm-1 was equivalent with salinity 2 mmhos cm-1 in producing dry weight of plant.Keywords: NaCl, Organic ameliorant Azolla pinnata, Rice, Salinity